The Effect of Capital Structure on Firm Value with Firm Size as a Moderating Variable in LQ45 Index Companies listed on the IDX in 2014-2023 - Khasanah, Isnaeni Nur; Situngkir, Tiar Lina (Fakultas Ekonomi Universitas Garut, 2025)
Increased public interest in investing needs to be supported by good company performance. The company's value determines the extent to which the company continues to grow. The corporation should optimize the capital structure and have the ability to manage the assets in the company well, hence improving the performance of the company.Â The objective of this test is to understand the influence of capital structure on firm value with company size as a moderating variable. Independent variable capital structure (Debt to Equity Ratio), dependent variable company value (Price Book Value), and moderating variable company size (Ln (total assets)). The population in the study were LQ45 index companies on the Indonesia Stock Exchange in 2014-2023,Â with 45 companies. The sample selected was 13 companies with predefined criteria using the purposive sampling method.Â The research method used is a quantitative approach using simple regression analysis and moderation regression analysis tests (MRA) using SPSS 25 analysis tools. The results of the research that has been done show that: 1). Capital structure affects the value of the company, 2). The size of the company strengthens the effect of capital structure on firm value.